A critical-analysis on the development of Energy Storage industry in China. (August 2018) - Tan, Zhongfu; Tan, Qingkun; Wang, Yuwei
Highlights: Our research focuses on Energy Storage industry. PEST-SWOT analysis is integrated into Energy Storage industry. The strategic analysis matrix of Energy Storage industry is constructed. Application distribution of energy storage industry. Abstract: With the combination of Internet, information technology and energy, energy storage industry plays an important role in the adjustment of energy structure with its abundant resources and friendly environmental benefits. Firstly, this paper introduces the status of energy storage industry, and studies the relevant policy documents, which lays the foundation for the internal and external ecological research of energy storage industry. Then, this paper uses PEST-SWOT strategic analysis model, based on PEST analysis, analyzes the strengths, weakness, opportunities and threats of energy storage industry in China. Finally, based on the results of PEST-SWOT analysis, the strategic analysis matrix of energy storage industry is constructed. The research results of this paper provide a strategic idea for the development of energy storage industry in China.